Video quality assessment of H.264 spatial scalable video coder - Hendrawan; Mahadhika, I. (2012 7th Telecommunications, Systems, Services, and Applications, 2012)
H.2646/Scalable Video Coding is the extension of H.264/Advanced Video Coding standard with higher coding efficiency. One of the video coding software having ability to do scalable video encoding process is JSVM (Joint Scalable Video Model) which uses H.264/SVC standard as the reference. On this paper, JSVM will be utilized to encode original video into stream having spatial scalability property. Afterward, in order to test the scalable video resulted from the encoding process, a set of system is prepared, including a server and three client devices having different screen resolutions. Subsequently, since it can be assured that the video is received at those clients, the original video is encoded again into few scalable videos with different compression ratio in order to identify the relation between compression ratio and video quality at each clients. These streaming tests are executed using IEEE 802.11n network. Evaluation of video quality and impairment on the client side is done by using Mean Opinion Score (MOS) from ITU-T Rec. P.910 and ITU-R Rec. BT.500-11. The result shows that all videos encoded spatially by JSVM software can be streamed and received at three different kinds of client. Moreover, the test indicates that not only the amount of compression ratio which affects subject's assessment of video quality, but also type of videos and client devices.